KOMUNIKASI PERSUASIF KOMUNITAS KONGKOW NULIS DALAM MENINGKATKAN BUDAYA MENULIS DI KALANGAN MAHASISWA KOTA PEKANBARU - Apriyani Caroline; Nova Yohana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The low level of culture of students writing caused by several factors such as the low reading interest, the assumption that writing is a difficult activitiy, and incorrect use of time, on a large scale will affect to the quality of human resources. Kongkow Nulis is a comunity that stands due to the low culture of writing among students, especially students in Pekanbaru. The persuasive effort of Kongkow Nulis in persuading strudents to improve their culture of writing is through their writing campaigns. This study aims to determine the credibility of communicators, messages, and methods of persuasion used by Kongkow Nulis Community to improve the culture of writing among students in Pekanbaru.This research uses qualitative descriptive research method adn using persuasive communication model of Apllebaum & Anatol. The reasearch informant consisted of Founder, co-Founder, 4 Members, and 2 Students from general circles had parcitipated in Kongkow Nulis activities selected bye using purposive techique. Data collections techniques were conducted throug interviews, non-participant observation, and documentation. To achieve the validity of the data in this study, the researcher used triangulation and reference adequacy.This results showed, first Kongkow Nulis community builds credibility as a communicator through two components, that is expertness and trust worthiness. Second, persuasive message consist of verbal and nonverbal messages. Verbal message conveyed are information about the authorship, such as steps to get started and get used to writing activities, tips and writing tricks, whose pattern is adopted from the programs of Kongkow Nulis through the use of languange with the components of clarity, assignments, and accurancy. As well as nonverbal messages through the use of colors and interesting designs, physical artifacts through work in the form of book, as well as vibrant, assertive and relaxed communicator intonation. Third, efforts in improving the writing culture are done through persuasion methods with approaches adapted to the cognitive, lifestyle, and emotional needs of students in Pekanbaru.Key Word : Persuasive Communication, Writing, Kongkow Nulis